GTAPINGAMS, version 9: Multiregional and small open economy models with alternative demand systems - Bruno Lanz; Thomas F. Rutherford (University of Neuchâtel, Institute of Economic Research (IRENE), 2016)
This paper describes the implementation in GAMS of an economic equilibrium model based on the GTAP version 9 dataset. We call this model and the ancillary programming tools GTAPINGAMS, version 9. Relative to previous installments of GTAPINGAMS, an innovation in this model is that it can easily switch between global multiregional (GMR) and small open economy (SOE) closures. We also include the possibility to evaluate results for alternatives representations of final demand, based on Cobb-Douglas preferences, linear expenditure system or the constant difference in elasticities function. In this paper we outline the model structure, document the associated equilibrium conditions and describe computer programs which calibrate the model to the desired regional and sectoral aggregation from the GTAP9 dataset. We perform a few calculations which illustrate how alternative structural assumptions influence the policy conclusions derived from the model.
Keywords: C6; C8; D5; F1; R1; 330; Applied economic analysis; Multiregional models; Small open economy models; Regulation; Trade policy; Computational models; Calibration